Superstitious Beliefs and Practices among The Fulbe in Nigeria: Causes, Types, Effects and Solutions from The Islamic Perspectives - Abubakar, Ahmad Yahaya; Gokaru, Shuaibu Umar (Journal Al-Muqaddimah, 2023)
Superstitious beliefs are cultural practices, which have been found in many cultures, ethnic groups and religions around the globe. The research aims at investigating the superstitious practices among Fulbe in Nigeria. It also looks into the causes, types and effects of superstitious beliefs and practices. The study area and as well provides some solutions from the Islamic perspective. The research adopts fieldwork and conventional research methods to gather the necessary research information. This is done by consulting previous research works done on the subject like journals, articles, textbooks and interviews conducted. The research discovers that ignorance made the Fulbe adopt these cultural practices. It also finds that some of these beliefs were generated based on false hope or fear of unknown circumstances. Islam attacks superstitious beliefs, thus it is revealed that it leads Muslim believers to go astray. The research concludes that piety will be achieved if Muslim should embark on seeking Islamic knowledge. And in this regard, Modibbe (scholars), Government and Islamic organization have important roles to play in Fulbe communities in Nigeria.